PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DAN DANA BAGI HASIL TERHADAP BELANJA MODAL (STUDI PADA KABUPATEN/KOTA DI WILAYAH ACEH) - Susi Susanti; Heru Fahlevi (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
The purpose of this study was to test the influence of local revenue (PAD), general allocation fund (DAU), sharing-revenue fund (DBH), and degree of decentralization againts capital expenditure in regencies / cities in Aceh region. The population in this study were all local governments in Aceh Region during 2011-2014. In Aceh, there are 23 districts / cities which consists of 18 counties and 5 cities.The method used in this research is census. The data used is secondary data obtained Budget Realization Report of the Provincial Finance Department. The analysis used is multiple linear regression analysis.The results showed that, together local revenue, general allocation fund (DAU), and sharing-revenue fund (DBH) againts capital expenditure in regencies / cities in Aceh region. Local revenue positive effect on capital expenditure in regencies / cities in Aceh Region. The general allocation fund has no effect on capital expenditure in regencies / cities in Aceh Region. Revenue-sharing is no effect on capital expenditure in regencies / cities in Aceh Region. Keywords: capital expenditure, fund local own revenue (PAD), general allocation fund (DAU), sharing-revenue fund (DBH)